2020
DOI: 10.1126/sciadv.abc7112
|View full text |Cite
|
Sign up to set email alerts
|

Potency and timing of antiviral therapy as determinants of duration of SARS-CoV-2 shedding and intensity of inflammatory response

Abstract: To impact the COVID-19 pandemic, lifesaving antiviral therapies must be identified. The number of clinical trials that can be performed is limited. We developed mathematical models to project multiple therapeutic approaches. Our models recapitulate off-treatment viral dynamics and predict a three-phase immune response. Simulated treatment with remdesivir, selinexor, neutralizing antibodies or cellular immunotherapy demonstrates that rapid viral elimination is possible if in vivo potency is sufficiently high. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
259
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(271 citation statements)
references
References 64 publications
11
259
0
1
Order By: Relevance
“…The antiviral drugs administered shortly after the onset of symptoms can shorten the course of clinical illness and it can reduce the infectiousness to others by reducing viral shedding ( Saber-Ayad et al, 2020 , Mitjà and Clotet, 2020 ). Goyal et al (2020) has performed a mathematical modeling to predict the impact of promising antiviral treatment. It has been reported that if a patient receives antiviral therapy in the early phase of infection, there are high chances that the duration of shedding and intensity of the effector immune response may decrease; however, there may be a limited impact on viral area under the curve (AUC) possibly owing to higher levels of early SARS-CoV-2 replication.…”
Section: Hit Early-hit Hard Principle With Antiviralsmentioning
confidence: 99%
“…The antiviral drugs administered shortly after the onset of symptoms can shorten the course of clinical illness and it can reduce the infectiousness to others by reducing viral shedding ( Saber-Ayad et al, 2020 , Mitjà and Clotet, 2020 ). Goyal et al (2020) has performed a mathematical modeling to predict the impact of promising antiviral treatment. It has been reported that if a patient receives antiviral therapy in the early phase of infection, there are high chances that the duration of shedding and intensity of the effector immune response may decrease; however, there may be a limited impact on viral area under the curve (AUC) possibly owing to higher levels of early SARS-CoV-2 replication.…”
Section: Hit Early-hit Hard Principle With Antiviralsmentioning
confidence: 99%
“…However, early initiation of antiviral therapy led to a lesser total viral load and a faster reduction of the load, which is consistent with results of other studies. 19 …”
Section: Resultsmentioning
confidence: 99%
“…For example, Goyal et al developed a mathematical model to predict the therapeutic outcomes of various COVID-19 treatment strategies. 19 Their model is based on target cell-limited viral dynamics 20 and incorporates the immune response to infection in order to predict viral load dynamics in patients pre- and post-treatment with various antiviral drugs. This model was used to project viral dynamics under hypothetical clinical scenarios involving drugs with varying potencies, different treatment timings postinfection, and levels of drug resistance, and the results of this study suggest the application of potent antiviral drugs prior to the peak viral load stage, i.e., in the presymptomatic stage, as an effective means of controlling infection in the body.…”
mentioning
confidence: 99%
“…g ., the variability of individual cells or the complex time course of virus release by individual infected cells). We have developed formal spatializations of a number of interesting ODE models of COVID, such as [ 61 , 62 ], to explore the effects of stochasticity of outcomes, the effects of spatial mechanisms, and infection dynamics at a particular site of infection on the predictions of these models. An additional benefit of our approach is that we can easily and consistently combine and integrate ODE models which focus on different aspects of the complex process of infection, spread and clearance ( e .…”
Section: Discussionmentioning
confidence: 99%
“…the local spread of virus or cytokine or the limited speed of movement of immune cells), or to additional factors which are difficult to include in an ODE model (e.g., the variability of individual cells or the complex time course of virus release by individual infected cells). We have developed formal spatializations of a number of interesting ODE models of COVID, such as [61,62], to explore the effects of stochasticity of outcomes, the effects of spatial mechanisms, and infection dynamics at a particular site of infection on the predictions of these models. An additional benefit of our approach is that we can easily and consistently combine and integrate ODE models which focus on different aspects of the complex process of infection, spread and clearance (e.g., combining published models of intracellular INF-induced viral resistance with spatial models of plaque spread in vitro [20,63]).…”
Section: Plos Computational Biologymentioning
confidence: 99%